Perceptions of Family Caregivers of Home-Dwelling Persons with Dementia regarding Access to Information and Involvement in Decisions - Henriksen, Nils Oddbjørn; Moholt, Jill-Marit; Blix, Bodil Hansen (Journal of Aging & Social Policy, 2020)
This cross-sectional study explored factors affecting information about available health services, content of services provided, and involvement in decisions regarding services as perceived by the family caregivers of home-dwelling persons with dementia in Northern Norway. Altogether, 788 family caregivers were invited to participate in a survey, with a response rate of 54.6% (n = 430). The respondents reported modest levels of perceived information and involvement. Few of the expected predictors were associated with the outcomes. Ordinal logistic regression analyses revealed that primary school as the highest level of education and perception of caregiving as moderately or very demanding predicted lower scores on family caregivers’ perceived level of information about available services, information on service content, and involvement in decisions. In addition, medium household income predicted lower scores on information about service content. The results may point to mechanisms that create inequalities in the processing of information and involvement in care decisions regarding care arrangements among different caregiver groups. Health authorities should investigate potential social inequalities in complementary health care for home-dwelling persons with dementia.